“This Is Not Our Disease”: A Qualitative Study of Influencers of COVID-19 Preventive Behaviours in Nguenyyiel Refugee Camp (Gambella, Ethiopia) - Tsegaye, Ademe; Wilunda, Calistus; Manenti, Fabio; Bottechia, Matteo; D'Alessandro, Michele; Putoto, Giovanni; Atzori, Andrea; Frehun, Daniel; Cardona-Fox, Gabriel (Frontiers in Public Health, 2022)
The COVID-19 pandemic has infected more than 263 million people and claimed the lives of over 5 million people worldwide. Refugees living in camps are particularly vulnerable because of difficulties implementing preventive measures and a lack of medical resources. However, very little is known about the factors that influence the behavioural response of refugees towards COVID-19. There is an urgent need for field evidence to inform the design and implementation of robust social and behaviour change communication strategies to respond to this threat in humanitarian settings. This study examines factors influencing refugee behaviour in the Nguenyyiel refugee camp in Gambella, Ethiopia, using data from focus group discussions and key informant interviews. Evidence suggests that while many factors facilitate the adoption of COVID-19 prevention measures, including knowledge about the virus and preventive strategies and engagement by community leaders and civil society, some important structural and cultural factors can hinder the uptake of preventive measures. This paper outlines the most significant. Overall, the study found that refugees perceived COVID-19 to pose a low threat (susceptibility and severity) and had mixed beliefs about the efficacy of preventive behaviours. This study also identified gaps in the existing information education and communication strategy. Awareness of COVID-19 is a necessary first step, but it alone is not sufficient to increase adoption of prevention measures in camps. Communication strategies must emphasise the threat posed by COVID-19 especially among the most vulnerable. Community support must increase and attention must be paid to behavioural incentives and barriers.